Faktor Yang Mempengaruhi Masyarakat Menjadi Buruh Tani Di Desa Sindangjawa Kecamatan Kadugede Kabupaten Kuningan - Ardiyansah Taufik; Turasih Turasih; Jalaludin Jalaludin (Empower : Jurnal Pengembangan Masyarakat Islam, 2024)
Employment issues remain a significant challenge under the current government. The lack of job opportunities forces people to take any available work to meet their daily needs, aligning with Scott's subsistence theory, which describes survival efforts to fulfill life necessities. Consequently, many turn to the informal sector as a survival strategy due to the lack of alternatives. This phenomenon is evident in Sindangjawa Village, where agricultural labor is highly demanded. Despite insufficient wages for agricultural workers, they do not shift to other sectors. This study aims to identify the factors influencing Sindangjawa Village residents to work as farm laborers and to examine the wages provided. Using descriptive qualitative research methods, data were collected through interviews and documentation. The study provides an overview of the conditions and symptoms observed in the field. The findings reveal that the primary factors driving Sindangjawa Village residents to choose agricultural labor are low education levels and inadequate transportation. The average education level in the village is junior high school (SMP), making it difficult for residents to compete for other jobs. Additionally, limited public transportation hinders access to urban areas. The seasonal nature of agricultural work is a significant challenge, as farm workers only earn during the planting and harvest seasons. In between these periods, finding work becomes difficult, making it hard for agricultural workers to meet their daily needs